PENGGUNAAN PEMBENTUKAN KATA BAHASA INGGRIS DALAM FACEBOOK - Jacobs, Stevani Wasti Philips (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This skripsi is entitled â€œPenggunaan Pembentukan Kata Bahasa Inggris dalam Facebookâ€. In present day, most of people use internet in their life. Internet offers a information of the world from one place to another. Besides, it is a helpful tool in communicating and researching all subject and help to connect with what we are learning to the real world. Communication is a medium to build a relation among people. People use language to do communication. In communication people use word to express their feeling and to deliver their idea. In other words they need words to communicate with others verbally or non-verbally. The objective of this research is to identify and to classify the use of word formation of clipping, blending, compounding, backformation, borrowing, acronym, and initialism based on the theories of Oâ€™Grady (1987), Lieber (2009) and supporting theory by Adam (2005). The result of this research shows that there are 7 kinds of English word formations that are used in Facebook, such as: clipping 20 data, blending 7 data, compounding 9 data, backformation 5 data, borrowing 6 data, acronym 7 data, and initialism 8 data. Besides, there is a new word formation process such as gr8, l8, n8, b4, f9, and cu used in Facebook which do not exist in English word formations based onÂ  Oâ€™Gradyâ€™s, Lieberâ€™s,Â  and Adamâ€™s theories. Keyword: English, Word Formation Usage, Facebook